Risk Factors of Thyroid Dysfunction in Patients With Type 2 Diabetes Mellitus - Ogbonna, Stanley U.; Ezeani, Ignatius U. (Frontiers in Endocrinology, 2019)
Background: Thyroid dysfunction has been widely reported among persons with diabetes (DM) in other parts of the World. In Nigeria, few studies have been reported. This study focused on risk factors for thyroid dysfunction in type 2 diabetes mellitus (T2DM) patients and will therefore add to the Nigerian literature, more so, as it is the first in South-East Nigeria. Objective: To determine the risk factors of thyroid dysfunction in patients with Type 2 DM. Methodology: Three hundred and fifty-four T2DM patients and 118 non-diabetic persons (controls) were recruited for the study. A pretested questionnaire was filled for each subject after due explanations. The subjects were subsequently examined and the findings, including anthropometric values and clinical parameters were documented. Their blood samples were tested for HbA1c, fT3, fT4, and TSH. Information retrieved from patients medical records included: age at diagnosis of DM, duration of DM, complications of DM. The Student's t-test, chi square test and regression analysis were used in the analysis of the data obtained. P < 0.05 was taken to be statistically significant. Results: About 56.5% of the T2DM patients who participated in this study were females and 62.7% of the controls were females. The T2DM patients had significantly higher BMI than controls (27.6 ± 5.0 kg/m2 vs. 26.2 ± 3.8 kg/m2, p = 0.002). Mean HbA1c was significantly higher in T2DM patients than in the controls (7.8 ± 2.0% vs. 5.8 ± 1.2%, p = 0.001). Female gender (OR = 3.8, p = 0.002), central obesity (OR = 2.5, 95%CI = 1.5–5.2, p = 0.001), DM nephropathy (OR = 4.8, p = 0.001), HbA1c ≥7% (OR = 4.3, p = 0.025) and duration of DM >5years (OR = 3.3, p = 0.012) were significantly associated with thyroid dysfunction in T2DM patients in this study. Conclusion: Female gender, central obesity, DM nephropathy, above normal HbA1c, and duration of DM were risk factors of thyroid dysfunction in type 2 DM patients in this study.